2006
DOI: 10.1177/0361198106197100114
|View full text |Cite
|
Sign up to set email alerts
|

Potential Uses of Transit Smart Card Registration and Transaction Data to Improve Transit Planning

Abstract: New automated fare collection systems being implemented on urban rail and bus transit systems offer the potential of tapping a rich source of customer usage data to improve transit planning. This is especially true of transit systems that offer smart cards as a payment option allowing long-term individual travel behaviors to be tracked and analyzed. This paper presents an initial analysis of the access and usage patterns of Chicago Transit Authority, Illinois, smart card holders during September 2004. The type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 2 publications
0
32
0
2
Order By: Relevance
“…Although the main purpose is to make charging and management more convenient [2], massive and continuous smart card data also can be recorded and served, which can provide lots of precious opportunities for researchers. The data can be used in various fields such as analysis of transit riders' travel patterns [3][4][5], behavior analysis [6][7][8][9], performance assessment of bus transport reform [10][11][12][13] and planning of the public transportation system [14][15][16][17]. In the study of smart card data, the spatio-temporal information on boarding and alighting is very important [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the main purpose is to make charging and management more convenient [2], massive and continuous smart card data also can be recorded and served, which can provide lots of precious opportunities for researchers. The data can be used in various fields such as analysis of transit riders' travel patterns [3][4][5], behavior analysis [6][7][8][9], performance assessment of bus transport reform [10][11][12][13] and planning of the public transportation system [14][15][16][17]. In the study of smart card data, the spatio-temporal information on boarding and alighting is very important [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, automatic fare collection (AFC) data such as smart card data have been used by transit service providers to analyze passenger demand and system performance. These data have been used for O-D matrices estimation [8,9], demand analysis [10,11], travel behavior analysis [12], operational management, and public transit planning [13][14][15], and so forth. In particular, there are emerging studies dealing with AFC data of URT systems.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing smart card data collected in Outaouis, Canada, Agard et al [1] have identified different trip habits based on the predefined user types and variabilities of trips against time. Utsunomiya et al [12] pointed out that demand pattern varies with day in week, therefore, different operation schedules should be provided for each day. Some researchers also focus on data processing methods and aim to get more meaningful information from smart card data.…”
Section: Introductionmentioning
confidence: 99%